2x+5+2x+3x=

Simple and best practice solution for 2x+5+2x+3x= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2x+5+2x+3x= equation:


Simplifying
2x + 5 + 2x + 3x = 0

Reorder the terms:
5 + 2x + 2x + 3x = 0

Combine like terms: 2x + 2x = 4x
5 + 4x + 3x = 0

Combine like terms: 4x + 3x = 7x
5 + 7x = 0

Solving
5 + 7x = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-5' to each side of the equation.
5 + -5 + 7x = 0 + -5

Combine like terms: 5 + -5 = 0
0 + 7x = 0 + -5
7x = 0 + -5

Combine like terms: 0 + -5 = -5
7x = -5

Divide each side by '7'.
x = -0.7142857143

Simplifying
x = -0.7142857143

See similar equations:

| 4(x-1)=-5(x+3)+32 | | -60x+32=Qx+p | | 5x+(2x-2)-(4x-3)= | | 3w+15=18 | | 3xy+9xy-5xy= | | 3(x-3)+2(x+2)=40 | | Y=4x^3-3x^2 | | F(x)=x^3-4x^2-5x | | 7(p+2)=-4(-4p-8) | | -2(5x+1)=-3-3x | | 3(5n-5)=-90 | | 9c=5(101)-160 | | z-10=28 | | -8(4x-3)+6x=-158 | | -8(3x+1)+5x=87 | | 91=7(-5a-2) | | 2n/3=11 | | -6(3x+5)=60 | | (9*9)-(8+4)= | | -6k+15=-5k+2k | | -10-(-63)= | | -117+4x=12x+107 | | (-5)+x=32 | | 900t-10t^2=0 | | 4(5-4x)-3x=96 | | 2(5-2x)=1.2(3x-5) | | 4(5-4x)-3x=97 | | -6(3x+4)=30 | | 2u-9=-7u | | Tan63=X/4 | | 10x-93=-x+94 | | 3+.05(4a+8)=9-2a |

Equations solver categories